Sustainable infrastructure investment : toward a more equitable future - Bruun, Eric Christian (New York, NY : Routledge, 2022)
"This book provides examples and suggestions for readers to understand how public investment decisions for sustainable infrastructure are made. Through detailed analysis of public investment in infrastructure over the last few decades in the United States, the United Kingdom, and Finland, the author explores how the decision-making processes for major public works spending, many of them requiring quite rigorous and detailed computational methodologies, can result in plans that underserve large portions of the population, are inequitable, and fail to efficiently preserve public property. Beginning with some of the commonly offered explanations for the slow pace of investment and repair in a supposedly prosperous society facing serious environmental challenges, the book then explores media's role in shaping the public-at-large's understanding of the situation and the unimaginative solutions put forward by politicians. It continues with some case studies of infrastructure investment, or lack thereof, including an exploration of competing uses for government funds. It concludes with some suggestions. It is aimed at a large readership of professionals, students, and policy makers in political science, urban planning, and civil engineering"--
OCLC-licensed vendor bibliographic record.
Keywords: Infrastructure (Economics); Public investments; Sustainable development; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning; ARCHITECTURE / Public, Commercial, or Industrial Buildings